Exploring pictorial representations of Jerome - Christina Mariella Fritz (Stridon)
This article examines the defining traits of Jerome as a translator in selected Western European paintings. Adopting the Translator Studies approach (Chesterman 2009), the research shifts focus from translated texts to the translator himself. To gain access to a translator through paintings, the study conducts an interdisciplinary analysis of pictorial-artistic representations, combining translation theory, art history, picture theory, and media analyses. By exploring eight Western European paintings, it reveals attributes and characteristics that identify Jerome as a translator. Additionally, it illustrates which depictions held greater prominence within the respective society, thereby facilitating a deeper understanding of the significance of Jerome’s translation of the Bible in a particular historical period.